To solve the equation for y, we first need to isolate y on one side of the equation.
Start by multiplying both sides of the equation by (5y + 3):
(-1)(5y + 3)/(5y + 3) = -7(5y + 3)/(5y + 3)
This simplifies to:
-1 = -7(5y + 3)
Next, distribute -7 to the terms inside the parentheses:
-1 = -35y - 21
To isolate y, add 35y to both sides:
35y + (-1) = -35y - 21 + 35y
Combine like terms:
35y - 35y = -21 + 1
0 = -20
The equation 0 = -20 is not true, so there is no solution for y in this equation.
Solve the equation for y.
−1 over 5y+3=−7
1 answer